STEAM Education: In Connection with Atal Tinkering Lab - Banerjee, Nandini; Ghosh, Sreya (Far Western Journal of Education, 2025)
This study explores the evolving concept of STEAM (Science, Technology, Engineering, Arts, and Mathematics) education and its implementation through India’s Atal Tinkering Labs (ATLs) in alignment with the National Education Policy (NEP) 2020. The primary objectives are to examine learners’ perceptions of STEM and STEAM, identify key elements and challenges in implementing STEAM education, assess its significance through ATLs, and propose strategic recommendations. Adopting a qualitative, descriptive research methodology, this study relies entirely on secondary data sources including academic literature, government policy documents, and ATL implementation reports. The findings highlight a positive shift in educational discourse toward interdisciplinary and hands-on learning, with STEAM education offering enhanced opportunities for creativity, critical thinking, and 21st-century skill development. However, the study also uncovers challenges such as lack of teacher training, infrastructural deficiencies, socio-economic barriers, and limited awareness, especially among rural and female students. The conclusion underscores that integrating STEAM education via ATLs can bridge the gap between theoretical and practical knowledge, fostering holistic development. For its effective implementation, systemic support, i teacher capacity building, and community awareness are essential. This study contributes policy-relevant insights and pedagogical strategies for mainstreaming STEAM education in Indian schools.